Statistical analysis for the pitch of mask-wearing Arabic speech - Hasan M. Kadhim; Alaa H. Ahmed; Saif A. Abdulhussien (Universitas Ahmad Dahlan, 2022)
The study is a comparison between the statistical properties of pitch (F0) for mask-wearing speech and unmasked. The speakers are Arab, of different ages and genders. A robust algorithm for pitch tracking (RAPT) is used for estimating F0. The subjective tests denote that masked speech is attenuated, and noisy-background speech has fewer F0 candidates. Using objective tests, 60% of female and male F0s do not change when wearing masks. The remaining 40% of speech F0s change (the percentage gross error), by an approximately 20% increase and 20% decrease. The percentage classification error is about 10%. The F0 changes in females younger than 12 years old are fewer compared with similarly-aged males. The F0 changes of females older than 12 years old were approximately equal compared with similarly-aged males. An average of F0 (M) is used for each speech to divide its F0 band (50-500) Hz into two bands, lower-band (LB) (50-M) Hz and upper-band (UB) (M-500) Hz. The attributes of the two bands have been statistically analyzed. The F0 classification error (CE) for females is higher than for males, but the gross error (GE) for males is higher than for females. The F0 change values are directly proportional to the probability of F0 change.